2007
DOI: 10.2224/sbp.2007.35.4.551
|View full text |Cite
|
Sign up to set email alerts
|

Self-Awareness and Cognitive Style: Relationships Among Adaption-Innovation, Self-Monitoring, and Self-Consciousness

Abstract: Adaption-innovation is a construct of preferred problem-solving style; adaptors work best within clear guidelines and prefer to “do things better”, whereas innovators bridle at structure and prefer to “do things differently”. Adaption-innovation bears considerable putative similarity to self-monitoring and self-consciousness. In this study the relationships among these constructs were explored using the responses of 55 undergraduate students (48 females, 7 males) on the Kirton Adaption-Innovation Inventory (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
0
16
0
2
Order By: Relevance
“…In the case of R&D staff, those whose job entails the carrying out of research, have been shown to have an intuitive cognitive style. Consequently managers should also train these staff to have competence in analytical cognitive style (Hutchinson, & Skinner, 2007;Jeurissen & Nyklicek, 2001;Neuman & Wright, 1999) so as to improve learning performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of R&D staff, those whose job entails the carrying out of research, have been shown to have an intuitive cognitive style. Consequently managers should also train these staff to have competence in analytical cognitive style (Hutchinson, & Skinner, 2007;Jeurissen & Nyklicek, 2001;Neuman & Wright, 1999) so as to improve learning performance.…”
Section: Discussionmentioning
confidence: 99%
“…Analytic cognitive style is characterized by precision, reliability, efficiency, discipline, and conformity, along with a preference for breaking down a problem, situation, or issue into its constituent parts in order to deal with it (Sadler-Smith, 1999a). Intuitive cognitive style is typified by undisciplined thinking and tangential approaches to tasks and problem solving that draw on a global perspective (Allinson & Hayes, 1996;Hutchinson & Skinner, 2007;Raisinghani, 2000;Rayner & Riding, 1997;Sadler-Smith, 1999a, 1999b. Conflicts produce different levels of learning performance, because of individual variations in information processing (Gardner & Korth, 1998;Kirkman & Roseb, 2000;Simons & Peterson, 2000).…”
Section: Moderating Effect Of Cognitive Stylementioning
confidence: 99%
See 2 more Smart Citations
“…According to Kirton (2003), cognitive style is founded on problem solving skills and creativity. Hutchinson & Skinner (2007) reported adoption-innovation is the constructs of cognitive style which can assume individual's problem solving behavior [4]. Kwang et al (2005) suggested that innovators have a propensity to repair the activity [5].…”
Section: Introductionmentioning
confidence: 99%